(untitled) (Journal of the College of Education for Women, 2019)
The study area is witnessing divergence where I am North wind North East wind as we find that the north wind is getting replicated as we move from the south, The reason can be attributed to the nature of the surface of the region, with at least repeat this wind the northern region to the presence of mountain ranges, while we find that energizes the surface in the center and south helped to increase repeat this wind gusts, It also finds that the North wind East prevail in the northern region and least replicated as we move from the north to the south and to the fact that North stations are within blowing this wind sites for the circles near the display of high pressure located centers to the north-east, north and distancing itself from paths depressions Movement , it is the use of Spearman correlation test and Taste of the relationship between the northern and north-eastern wind with the heat and humidity coefficient shows the following : there was a significant correlation between temperatures and winds in the North all stations except stations Mosul district, And no significant relationship between temperature and wind North East , kzlk turned out to be no significant relationship between the northern and north-eastern wind and humidity.